Hate Speech During the Caliphate of ‘Alī ibn Abī Ṭālib and Its Relevance to Regulations in Indonesia: The Study of the Islamic Law History - Yayan Muhammad Royani (Al-Ahkam, 2021)
This paper aims to describe the process of overcoming hate speech crimes during the caliphate of 'Alī ibn Abī Ṭālib in the perspective of the history of Islamic law. The important question to be answered in this paper is how did the caliph 'Alī ibn Abī Ṭālib contribute to handling the problem of hate speech? This paper finds three essential things. First, the death of Caliph 'Uthmān became the cause of the emergence of various slander. The main perpetrators were the Sabā’iyyah, Khawarij, and Shia groups. The form of slander is in the form of hate speech, such as insulting, defaming, inciting, spreading hoaxes which are violations of human rights and have discriminated against certain entities and individuals. Second, the policy of overcoming hate speech is pursued by a criminal and social law approach. Third, the relevance between ‘Alī ibn Abī Ṭālib's policy and existing regulations in Indonesia lies in the form of actions, punishments, and protection of human rights from discrimination.